Polarization-dependent orientation of LiNbO3:Eu3+ nanocrystals using ultrashort laser pulses in borosilicate glasses - Ari, Julien; Cavillon, Maxime; Lancry, Matthieu; Poumellec, Bertrand (Advanced Optical Technologies, 2023)
Femtosecond (fs) laser writing is a flexible way to induce three-dimensional local structural modifications inside glass materials, such as crystallization. The latter is a function of both glass composition, hence properties, and laser parameters. Previous works have shown that a glass composition of 33Li2O–33Nb2O5–13SiO2–21B2O3 (LNSB) mol% yields to crystallization of laser polarization orientable LiNbO3 nanocrystals upon irradiation with a 1,030 nm fs laser. In this paper, we present the effects of rare earth incorporation in the glass composition [i.e., europium (0.5, 1, and 2 mol%)] on the crystallization process of LiNbO3 nanocrystals induced by fs laser irradiation. The embedding of Eu3+ ions into these nanostructures has an interest in developing new integrated and miniaturized optical lasers and amplifiers in visible wavelengths. The influence of laser parameters, such as repetition rate (RR), pulse energy, and polarization, has been studied. Irradiated areas are investigated using optical and electron microscopy techniques. The effect of Eu3+ concentration on the crystallization behavior (crystal formation and morphology) is discussed, as Eu2O3 is not acting as a nucleation agent in LNSB glass up to 2 mol%.